Cartographier l’ontologie d’un territoire sur le web - Diego Landivar; Alexandre Monnin; Emilie Ramillien (Netcom)
Under what conditions is it possible to define the identity of a territory on the Web? In this paper we explore the way entities with a clear-cut geographical existence (such as Bolivia) exist and are objectivized in a digital space like the Web. Our question is “should the mapping of a territorial entity on the Web and its traditional geographical representation converge?” In order to answer it, we set out an analysis which takes as its starting point the architecture of the Web, revolving around the notion of resource (objects identified on the Web). Therefrom, we conduct an anthropological analysis of the “modes of existence” (Etienne Souriau) of a country such as Bolivia on the Web. We use several digital methods in order to probe concrete examples of the networks of associations it elicits and show that, as a resource, its limits that are widely redefined on the Web, largely through the networks generated by online participation (blogs, commentaries, tweets, Wikipedia entries…). Bolivia can thence be described as a burgeoning, quite unstable, entity whose borders become rather imprecise. Yet, such a characterization also proves way more encompassing and richer than traditional (namely, geographic) ones.